2013
DOI: 10.3747/co.20.1301
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Response to Imatinib Mesylate in Cutaneous Mastocytosis Associated with Chronic Myelomonocytic Leukemia

Abstract: 1 major and 1 minor, or 3 minor World Health Organization diagnostic criteria, which are listed in Table ii 4 . Although cutaneous and systemic involvement can occur together in adults, children rarely experience systemic manifestations and often have self-limiting disease [5][6][7] . The treatment of sm in adults remains a challenge, in part because of its chronicity and heterogeneity. CASE DESCRIPTIONA 67-year-old white woman presented with progressive and debilitating pruritus of 5 years' duration.Her sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Overall, 46 patients with mastocytosis lacking the D816V KIT mutation and other extracellular membrane/transmembrane KIT mutations who were treated with imatinib and further evaluated for response to therapy have been reported, with an overall response rate of 80% (37/46 cases) [ 18 , 32 35 , 37 , 42 , 45 62 ]. However, almost one third of such responding cases corresponded to patients with SM associated with either HES/CEL ( n = 11/37) [ 32 , 34 , 37 , 45 47 ] or chronic basophilic leukemia ( n = 1/37) [68] carrying rearrangements of PDGFR α/ PDGFR β; in turn, another 10/37 patients only showed improvement of MC-mediator release-associated symptoms and/or skin lesions [ 32 , 48 , 51 , 52 , 55 , 57 ] Among the remaining 15 cases, 5 fulfilled criteria for CR [ 18 , 49 , 51 , 53 , 54 ] and 10 were reported to have PR [ 32 , 45 , 49 , 50 , 56 ]. It should be noted that unlike CR, which was defined in all reports by the disappearance of all mastocytosis-related signs and symptoms together with decrease of sT levels to < 20 μg/L, criteria used for establishing PR were more heterogeneous, a significant reduction of BM MC infiltrates being documented in only 4/10 PR patients [ 32 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 46 patients with mastocytosis lacking the D816V KIT mutation and other extracellular membrane/transmembrane KIT mutations who were treated with imatinib and further evaluated for response to therapy have been reported, with an overall response rate of 80% (37/46 cases) [ 18 , 32 35 , 37 , 42 , 45 62 ]. However, almost one third of such responding cases corresponded to patients with SM associated with either HES/CEL ( n = 11/37) [ 32 , 34 , 37 , 45 47 ] or chronic basophilic leukemia ( n = 1/37) [68] carrying rearrangements of PDGFR α/ PDGFR β; in turn, another 10/37 patients only showed improvement of MC-mediator release-associated symptoms and/or skin lesions [ 32 , 48 , 51 , 52 , 55 , 57 ] Among the remaining 15 cases, 5 fulfilled criteria for CR [ 18 , 49 , 51 , 53 , 54 ] and 10 were reported to have PR [ 32 , 45 , 49 , 50 , 56 ]. It should be noted that unlike CR, which was defined in all reports by the disappearance of all mastocytosis-related signs and symptoms together with decrease of sT levels to < 20 μg/L, criteria used for establishing PR were more heterogeneous, a significant reduction of BM MC infiltrates being documented in only 4/10 PR patients [ 32 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 In the experience of some authors, effective treatment with imatinib in CM has been reported. 24 what's more, with good tolerance of treatment. 26 To summarize, although the disappearance of skin lesions has been reported because of cytoreductive therapies in SM, the use of potentially toxic drugs in CM is not recommended.…”
Section: Discussionmentioning
confidence: 96%
“…However, complete and permanent resolution of skin lesions is not achieved with mentioned therapies . Interestingly, partial or complete remission of cutaneous symptoms was observed in some patients with SM treated with cytoreductive therapy . Generally, interferon‐ α is not recommended in purely CM because of serious side effects of the therapy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations